Population health partnerships and social capital: Facilitating hospital-community partnerships - Cory E. Cronin; Berkeley Franz; Sarah Garlington (Elsevier, 2021)
Social capital refers to the social norms and networks that build trust and enable individuals to pursue shared objectives; it can vary considerably between communities and across time. Considerable evidence suggests that the presence of social capital at the local or state level is associated with improved individual health and lower community-level mortality, chronic illness, and diseases of despair such as substance abuse. Social capital may influence health outcomes because community-engaged institutions are more common in communities with strong social bonds and cross-sector partnerships are more easily leveraged. This study examines the impact of social capital on the effectiveness of health care organizations, specifically hospitals, in establishing population health partnerships which are critical for addressing health disparities and reducing preventable deaths. In a national sample of hospitals, we find that in communities with high social capital, hospitals are more likely to hold partnerships with public health and social service agencies. Social capital within communities may create the conditions in which hospitals are able to easily identify possible partnerships and engage in collaborative efforts to improve population health.